V2O5 nanobelts via a facile water-assisted strategy boosting electrochromic performance. (1st March 2023) - Sun, Haohao; Wang, Wenxuan; Fan, Qiongzhen; Qi, Yanyuan; Xiong, Yuli; Jian, Zelang; Chen, Wen
Abstract: Vanadium pentoxide (V2 O5 ) has an open layered structure with vanadium ions in various oxidation states, displaying great potential for application in electrochromic. Herein, one-dimensional (1D) V2 O5 nanobelts were successfully synthesized using a facile water-assisted strategy of stirring and sonicating in water without adding any other chemical reagents. The V2 O5 nanobelts are lengths of a few micrometers and widths of tens of nanometers, especially, displayed expanded layered structure with a d-spacing of 11.7 Å, accelerating the Li +  diffusion kinetics. The electrochromic property of the V2 O5 nanobelts film was investigated. It demonstrates that V2 O5 nanobelts are multicoloured electrochromic (yellow, yellow-green, and steel grey) with high transmittance modulation (54.8% at 427 nm), fast response time (9.0 s for bleaching and 2.7 s for coloring at 427 nm), and long cycle stability (1000 cycles). The electrochromic device based on V2 O5 nanobelts also exhibits outstanding transmittance modulation and fast response time. This work develops a green large-scale preparation method to synthesize outstanding V2 O5 -based electrochromic materials.